EXTRAPOLATION OF DESIGN GUIDELINES DURING THE CONCEPTUAL DESIGN PHASE: A METHOD TO SUPPORT PRODUCT ARCHITECTURE DESIGN. (May 2020) - Formentini, G.; Favi, C.; Bouissiere, F.; Cuiller, C.; Dereux, P.-E.; Guillaume, R.; Malchair, C.
Abstract: The work aims at the definition of a design methodology able to drive designers in the definition of product architectures, starting from rough information available at the conceptual design. The methodology identifies design guidelines useful for the development of product architectures optimized for a given target (i.e. assembly, cost). The methodology is based on domains which combine attributes related to a specific aspect of the target. The exploratory application of the methodology was performed to address the equipment installation of a civil aircraft for assembly/installation target.